A pending issue that does not disappear: the need to implement a policy of search of missing persons parting from the establishment of a central agency in the Peruvian State - Lengua Parra, Adrián (2015)
As a product of the armed violence and the human rights violations committed in the decades of the eighties and nineties, the Peruvian government initiated a process of transitional justice in order to compensate the victims and reconcile a fragmented and divided society. However, there are still issues pending in that matter. One of these issues is the search of the missing persons.The present article will delve into the importance of a policy of search of missing persons in the light of the international obligations on human rights matters of the Peruvian state, and will analyze the weaknesses of their judicial actions to accomplish this task. The need of a centralized organism in charge of this function will be sustained, and a normative proposal for its implementation in the Peruvian legal system will be presented.